Fibroblast-to-myofibroblast transition in bronchial asthma - Michalik, Marta (Cell Mol Life Sci, 2018)
Bronchial asthma is a chronic inflammatory disease in which bronchial wall remodelling plays a significant role. This phenomenon is related to enhanced proliferation of airway smooth muscle cells, elevated extracellular matrix protein secretion and an increased number of myofibroblasts. Phenotypic fibroblast-to-myofibroblast transition represents one of the primary mechanisms by which myofibroblasts arise in fibrotic lung tissue. Fibroblast-to-myofibroblast transition requires a combination of several types of factors, the most important of which are divided into humoural and mechanical factors, as well as certain extracellular matrix proteins. Despite intensive research on the nature of this process, its underlying mechanisms during bronchial airway wall remodelling in asthma are not yet fully clarified. This review focuses on what is known about the nature of fibroblast-to-myofibroblast transition in asthma. We aim to consider possible mechanisms and conditions that may play an important role in fibroblast-to-myofibroblast transition but have not yet been discussed in this context. Recent studies have shown that some inherent and previously undescribed features of fibroblasts can also play a significant role in fibroblast-to-myofibroblast transition. Differences observed between asthmatic and non-asthmatic bronchial fibroblasts (e.g., response to transforming growth factor β, cell shape, elasticity, and protein expression profile) may have a crucial influence on this phenomenon. An accurate understanding and recognition of all factors affecting fibroblast-to-myofibroblast transition might provide an opportunity to discover efficient methods of counteracting this phenomenon.